Genetic Disorders a Bird View - Patil, Dr. Swapnil S.; Patil, Dr. R. B.; Lokhande, Dr. Smita V. (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Impairment in an individual DNA leads to the occurrence of genetic disorders. There are different factors which leads to the alteration in gene, chromosome. The alteration addition or deletion of particular gene or segment of chromosome leads to particular disease. Here effort has been done to summarize and analyze the different genetic disorders.